Do children with ASD have difficulty handwriting under time pressure?. (May 2017) - Grace, N.; Rinehart, N.J.; Enticott, P.G.; Johnson, B.P.
Highlights: Children with ASD appear to have some capacity to compensate for underlying motor impairment when completing a well-practiced writing task. There were no group differences in regard to handwriting errors and/or spacing between words in either condition. The relationship between intellectual skills and handwriting performance is highly complex. Abstract: Background: Children with autism spectrum disorder (ASD) often experience significant handwriting impairment, however the influence of time pressure on overall performance is unclear. The aim of the current study was to characterise the handwriting profile of children with ASD across both non-speeded and speeded conditions, with particular focus given to spacing difficulties and handwriting errors. A further aim was to explore the relationships between handwriting and both intellectual and motor skills under different task conditions. Method: Boys with ASD ( n = 23) and matched controls ( n = 20) aged 8–12 years completed a modified version of the speed subtest of the Handwriting Performance Test, which allowed for both an ecologically valid and relatively simple motoric task. Participants wrote a simple phrase ( cat and dog ) five times in each condition. Results: No significant group differences were identified for handwriting errors or spacing between words in either condition, however the ASD group demonstrated greater variability relative to controls, particularly in the speeded condition. Significant negative associations were identified between motor proficiency and handwriting errors in the non-speeded condition. Conclusions: While motor processes are shown to have a significant role in overall handwriting proficiency, it appears that motor ability may influence the handwriting process to different degrees, depending on the nature of the task employed. A lack of group differences with respect to handwriting errors and spacing between words may suggest that children with ASD have the ability to compensate for underlying motor impairment when completing a well-practiced writing task.